Impact of COVID-19 Pandemic on COMPI Fertility Problem Stress Scale and the State-Trait Anxiety Scale in Patients Undergoing IVF/ICSI - Arzu Yurci; Saban Karayagiz (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: This study aimed to investigate the effect of the COVID-19 outbreak on infertile couples dealing with stress and anxiety during in vitro fertilization treatment.